Distribution, incidence and severity of viral diseases of yam (Dioscorea spp.) in Cote dIvoire - Yeyeh, M.N.Y.; Diallo, H.; Akinbade, S.; Séka, K.; Kumar, P. Lava (Academic Journals, 2014)
A survey was conducted in major yam cultivation zones in Côte d’Ivoire in 2009 to determine the incidence, severity of viral diseases, and viruses associated with the infected plants. Incidence and severity of the viral diseases were estimated based on symptoms. Enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR)-based techniques were used for the detection of Yam mosaic virus (YMV), Cucumber mosaic virus (CMV), Dioscorea mottle virus (DMoV) and yam badnaviruses in the sampled yam leaves. Disease incidence varied from 0 to 90% and symptom severity from 1 to 5. There were significant difference in incidence and severity between different agro-ecological zones (P < 0.001). About 36% of the samples tested positive to YMV, ca. 1.5% tested positive to CMV, ca. 39.1% samples tested positive to yam infecting badnaviruses, and none of the samples tested positive to DMoV. This study demonstrated high incidence of virus diseases in all the yam production regions and warrants implementation of virus disease control measures.